A Nonstoichiometric Niobium Oxide/Graphite Composite for Fast‐Charge Lithium‐Ion Batteries. Issue 26 (26th May 2022) - Li, Tongtong; Liu, Kuanting; Nam, Gyutae; Kim, Min Gyu; Ding, Yong; Zhao, Bote; Luo, Zheyu; Wang, Zirui; Zhang, Weilin; Zhao, Chenxi; Wang, Jeng‐Han; Song, Yanyan; et al.
Abstract: Electrification of transportation has spurred the development of fast‐charge energy storage devices. High‐power lithium‐ion batteries require electrode materials that can store lithium quickly and reversibly. Herein, the design and construction of a Nb2 O5−δ /graphite composite electrode that demonstrates remarkable rate capability and durability are reported. The presence of graphite enables the formation of a dominant Nb12 O29 phase and a minor T‐Nb2 O5 phase. The high rate capability is attributed to the enhanced electronic conductivity and lower energy barriers for fast lithium diffusion in both Nb12 O29 and T‐Nb2 O5, as unraveled by density functional theory calculations. The excellent durability or long cycling life is originated from the coherent redox behavior of Nb ions and high reversibility of lithium intercalation/deintercalation, as revealed by operando X‐ray absorption spectroscopy analysis. When tested in a half‐cell at high cycling rates, the composite electrode delivers a specific capability of 120 mAh g –1 at 80 C and retains over 150 mAh g –1 after 2000 cycles at 30 C, implying that it is a highly promising anode material for fast‐charging lithium‐ion batteries. Abstract : A nonstoichiometric niobium oxide/graphite composite is developed as a high‐rate anode. Because of the low lithium diffusion barriers in both Nb12 O29 and T‐Nb2 O5, and the high electronic conductivity resulting from non‐stoichiometry and the presence of graphite in the electrode architecture, the composite enables high‐rate capability and durability.